“Because I said so.” – Collection and evaluation of parenting phrases in German-speaking samples - Erika Kljucak; Nourat N. Alazza; Pia Hemme; Louisa Kulke (PLoS ONE, 2026)
Verbal communication is a key aspect of parenting behaviour. However, phrases frequently used in parenting situations (e.g., “Stop crying”, “I love you”) have yet to receive focused attention in the research literature. This set of two online questionnaire studies investigated the use of parenting phrases within a German-speaking sample. The first study compiled an inventory of common parenting phrases, contextualized them within parenting style research on the dimensions of warmth and control, and examined their associations with self-esteem. A total of 309 phrases were collected, of which the 84 most frequently mentioned were further analysed in Study 2, which examined their ratings within a communication theory perspective and investigated socio-demographic influences on participants’ evaluations. Participants reported hearing more negative and fewer positive phrases from their caregivers than they reported using towards their own children. Similarities between the frequency of negative or positive phrases heard during participants’ upbringing and the frequency of phrases from those categories used with their own children could not be found. Neither parental warmth and control nor exposure to self-esteem-related phrases were significantly associated with self-esteem. Age differences in experienced parenting phrases and parenting phrase usage were observed, as younger participants reported hearing more positive phrases and using fewer negative phrases than older participants. In Study 2, the ratings of the parenting phrases were related to participants’ age and experienced parenting during childhood, but no association was found with parental status. Exploratory results from both studies align with the Relational Framing Theory, suggesting it may serve as a useful addition to traditional parenting style theories in interpreting caregiver-child communication. These studies provide a foundation for investigating parenting phrases, thereby offering a novel perspective on parental communication – a crucial factor in shaping child development and family dynamics.